Psychological Conflict Experienced by Characters in the Drama Lautan Bernyanyi by Putu Wijaya - Hidayanti Ali, Ayu; Kadir, Herson; Sukma Wati, Ni Gusti Ayu; Ariyanti Daud, Olvi Dwi; Halaa, Siti Salsadila (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
The psychological conflict experienced by the characters in the drama Lautan Bernyanyi by Putu Wijaya reflects the complexity of the human mind in dealing with pressure, alienation, and fear. Through a literary psychology approach, this study focuses on the inner struggle of the main characters, especially Captain Leo and Comol. The method used is qualitative descriptive with a literature study technique, namely by reading and intensively observing the drama script Lautan Bernyanyi, which is then analyzed using literary psychology theory. The results of the study show internal conflict, conflict between rationality and myth, and existential struggle within the characters. Identity crisis, need for acceptance, and cultural pressure are factors that influence the mental condition of the characters. This drama reflects how psychological forces can shape or even destroy an individual's existence in extreme situations.